2021
DOI: 10.18502/kls.v6i1.8633
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Predictor of Self-Management Behavior Practice Among People with Type 2 Diabetes Mellitus (T2DM)

Abstract: Diabetes mellitus is a major health challenge associated with morbidity and mortality. Self-management behaviors are a critical part of diabetes disease management. Empowered or activated patients are more likely to practice better implementation of self-management behaviors. However, self-management behavior practice has not always been applied effectively among these populations. Further investigations are necessary to evaluate the status and factors that influence the practice of selfmanagement behaviors am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…This is an important theoretical viewpoint of planned behaviour theory 22. Clara et al 23 found that patients with better self-efficacy had higher levels of self-management. Risk perception refers to the subjective perception of the likelihood that a negative health-related event will occur for a certain person or group of people in a particular period 24.…”
Section: Methodsmentioning
confidence: 99%
“…This is an important theoretical viewpoint of planned behaviour theory 22. Clara et al 23 found that patients with better self-efficacy had higher levels of self-management. Risk perception refers to the subjective perception of the likelihood that a negative health-related event will occur for a certain person or group of people in a particular period 24.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 72 articles were evaluated for eligibility, and 65 were excluded because they did not meet the inclusion criteria, which included populations with type 1 DM patients or other types, the articles were not about self-efficacy, the results were inappropriate, and the articles were literature reviews and qualitative studies. Seven articles from database searches (12)(13)(14)(15)17,25,26); and two articles from citation searches with full-text readings (16,20), where nine articles were included in this systematic review. Figure 1 details the study selection procedure.…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 3 shows the characteristics of study participants among nine studies, of which seven studies were conducted in Asian countries, including two studies conducted in Indonesia (13,15), one study conducted in Malaysia (20), Saudi Arabia (16); Iraq (17); Turkey (14); and China (26). Furthermore, two studies were conducted in African countries, Sudan (12) and Ethiopia (25).…”
Section: Study and Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semakin tinggi efikasi yang dimiliki seseorang maka semakin tinggi pula perilaku manajemen diri orang tersebut, karena orang yang memiliki manajemen diri yang tinggi cenderung lebih kuat dan gigih dalam berusaha mencapai kinerja yang maksimal. Penderita DMT2 yang memiliki efikasi diri yang tinggi cenderung berusaha semaksimal mungkin untuk merubah perilaku dan mengontrol dirinya agar memiliki hidup yang sehat (Clara et al, 2021).…”
Section: Efikasi Diri Dan Manajemen Diriunclassified